Characterization of Pectobacterium brasiliense strains from potato and vegetables in Israel. (30th August 2021) - Tsror (Lahkim), Leah; Hélias, Valerie; Mordechai‐Lebiush, Sara; Erlich, Orly; Hazanovsky, Marina; Chalupowicz, Laura; Reuven, Michal; Dror, Orit; Valinsky, Lea; Laurent, Angelique; Manulis‐Sasson, Shulamit
Abstract: Pectobacterium brasiliense (Pbr) infects a wide range of crops worldwide, causing potato blackleg and soft rot and vegetable soft rots. This study aimed to characterize the genetic diversity and virulence variability among 68 Pbr strains isolated from either symptomless potato progeny tubers, diseased potato plants, ware potatoes wash water, or vegetables grown in Israel, as well as strains isolated from symptomless seed tubers grown in Europe, or diseased potato plants grown in France. The collection was typed using PCR and TaqMan real‐time PCR analyses, dnaX sequence analysis, pulsed‐field gel electrophoresis (PFGE), and pectolytic activity. dnaX phylogeny grouped almost all strains in a common genetic clade related to Pbr, which was distinct from the other Pectobacterium species. PFGE analysis identified two main clusters, including one major group of 47 strains with 95%–100% similarity. Maceration assays on two potato cultivars showed significant differences between strains but with no correlations with the source of the strains nor the status of the host (with/without symptoms). Molecular ( dnaX sequences and PFGE profiles) and phenotypic analyses (tuber maceration tests) showed that the tested Pbr strains are not a homogeneous group. Analysis of the tested Pbr strains isolated from potato and vegetables grown in fields with a history of potato cultivation suggests that seed tubers imported from Europe may be the main source for Pbr in Israel. To the best of our knowledge, this is the first study that describes biodiversity and population structure of P. brasiliense isolated from potato and vegetables under hot climate conditions. Abstract : dnaX sequences, PFGE profiles, and tuber maceration tests showed that Pectobacterium brasiliense strains from symptomless potato tubers, diseased potato plants, ware potatoes wash water, and vegetables are not a homogeneous group.